Perceptions of Young Adults on the Critical Success Factors of the Build-to-Rent Housing Model in Sydney, Australia - Rotimi Boluwatife Abidoye; Janet Ge; Albert Agbeko Ahiadu; Chibuikem Michael Adilieme; Samuel Swanzy-Impraim (Buildings, 2023)
Amid Australia’s surging house prices, rental housing has become the safety net for young adults experiencing housing stress. The attention of policymakers is drawn towards the build-to-rent (BTR) housing model, a growing housing option for many young Australian adults. Although BTR’s integration into Australia’s housing and planning landscape is unfolding, the perception of young adults is lacking in policy reforms for this growing industry. This study examines the perspectives of young adults aged 18 to 34 years on the critical success factors (CSFs) of the BTR housing provision in Australia. The responses are analysed using an explanatory factor analysis, relative importance index, and ANOVA. Our findings show a critically low awareness of BTR among young adults in Australia. Respondents, between 18 and 24 years, are most concerned with public awareness, an indication of their desire for transparency and engagement in decision making at the policy level. Young adults rank regulation and government policy interventions as the most important CSF of BTR housing. This shows that they are more concerned about the affordability of BTR houses. This study concludes that young adults’ viewpoints on BTR are important in ongoing policy reforms. There is a need to ensure that this asset class is accessible and affordable to this target group.